DOES QURAN HARBOR HATRED TOWARDS JEWS? (Hermeneutical Exploration of Surah Al-Baqarah: 120) - Akbar, Irwan Ahmad (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2024)
This research explores the verses related to Jews in the Quran, particularly in Surah al-Baqarah verse 120. Some groups claim this verse to be evidence that the Quran harbors hatred towards Jews. This research utilizes a historical and semantic approach to thoroughly examine the verses in the Quran that pertain to Jews. This is conducted to produce a definitive answer to the question: does the Quran indeed hate Jews? Using a qualitative approach with data from classical and modern Islamic literature, this research concludes that the Jews referred to in the Quran, especially in Surah al-Baqarah verse 120, are a prototype of an antagonistic character. Through a semantic-historical analysis, it is determined that the Jews referred to in the Quran do not represent all Jews, but specifically denote the Jewish groups in Medina. The Quran does not hate Jews; rather, it criticizes their behavior, not their race or religion. In summary, the Quran critiques bad behavior from any individual, regardless of who they are.